2012
DOI: 10.1074/jbc.m111.295121
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided Engineering Enhances a Phytochrome-based Infrared Fluorescent Protein

Abstract: Background: Engineered variants of the phytochrome photoreceptor are infrared fluorescent proteins. Results: Based on crystal structures, side chain substitutions near the chromophore were combined with monomerization of truncated phytochrome to yield an enhanced fluorophore. Conclusion: Amino acid changes that increase fluorescence discourage photoproduct formation. Significance: This improved infrared phytofluor provides long-wavelength excitation for high signal to noise in tissue and whole animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
257
2
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(283 citation statements)
references
References 34 publications
11
257
2
13
Order By: Relevance
“…The aliphatic face is flanked by a compatible environment provided by conserved hydrophobic residues (e.g., , whereas the hydrophilic face hydrogen bonds with an ordered water and the imidazole of an invariant histidine (His-290). Not surprisingly, mutational studies showed that most, if not all, of the conserved amino acids surrounding the bilin are critical to proper photochemistry (Fischer and Lagarias, 2004;Hahn et al, 2006;Yang et al, 2007Yang et al, , 2008Wagner et al, 2008;Ulijasz et al, 2009;Auldridge et al, 2012;Burgie et al, 2013Burgie et al, , 2014b. In fact, a number of variants impacting the chromophore binding pocket fail to photoconvert to Pfr in red light and instead are highly fluorescent.…”
Section: Gaf Domain and Bilin Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…The aliphatic face is flanked by a compatible environment provided by conserved hydrophobic residues (e.g., , whereas the hydrophilic face hydrogen bonds with an ordered water and the imidazole of an invariant histidine (His-290). Not surprisingly, mutational studies showed that most, if not all, of the conserved amino acids surrounding the bilin are critical to proper photochemistry (Fischer and Lagarias, 2004;Hahn et al, 2006;Yang et al, 2007Yang et al, , 2008Wagner et al, 2008;Ulijasz et al, 2009;Auldridge et al, 2012;Burgie et al, 2013Burgie et al, , 2014b. In fact, a number of variants impacting the chromophore binding pocket fail to photoconvert to Pfr in red light and instead are highly fluorescent.…”
Section: Gaf Domain and Bilin Architecturementioning
confidence: 99%
“…Whereas the pyrrole nitrogen of the flipped D-ring assumes a large displacement to hydrogen bond with the carboxylate of Asp-207, the aliphatic functional groups remain nestled in their hydrophobic environment, which shifts commensurately by rotamerization of the Tyr-176 and Phe-203 side chains (Yang et al, 2009). As revealed by spectroscopic and crystallographic analyses of the Asp-207 mutants (Hahn et al, 2006;von Stetten et al, 2007;Wagner et al, 2008;Auldridge et al, 2012;Burgie et al, 2014b), this D-ring/ Asp207 connection is critical for acquisition of the Pfr state as well as for preventing incorporation of more cyclic tetrapyrroles into the GAF domain pocket.…”
Section: Gaf Domain and Bilin Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Excitation triggers, instead, a reversible photoreaction of the chromophore. The structural basis for adapting the chromophore to its different functions is important not only for understanding photosynthetic energy transfer but also for designing artificial photosynthetic systems (5) and for engineering fluorescent biomarkers (18,19). In AP-B, the extreme red-shifted absorbance has recently been attributed to the planar geometry of the PCB chromophore on the ApcD subunit (6).…”
mentioning
confidence: 99%
“…The spectra of dark-adapted protein which was protected from light for Ն3 h (Pr state) or illuminated with red light for 1 min (mixed Pr state/Pfr state) were collected. Proteins were illuminated with light from a Fostec ACE source filtered with a 700-Ïź 5-nm-band-pass filter (Andover Corp., Salem, NH), which delivered irradiance of 140 mol/m 2 /s, as previously described (31). Illuminated-state measurements were limited to spectra recorded no less than 10 s after light stimulus removal, by which time thermal reversion was under way.…”
Section: Methodsmentioning
confidence: 99%